2020
DOI: 10.3390/biomedicines8090369
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Electrical Stimulation of the Superior Laryngeal Nerve in the Rat: A Potential Therapeutic Approach for Postmenopausal Osteoporosis

Abstract: Electrical stimulation of myelinated afferent fibers of the superior laryngeal nerve (SLN) facilitates calcitonin secretion from the thyroid gland in anesthetized rats. In this study, we aimed to quantify the electrical SLN stimulation-induced systemic calcitonin release in conscious rats and to then clarify effects of chronic SLN stimulation on bone mineral density (BMD) in a rat ovariectomized disease model of osteoporosis. Cuff electrodes were implanted bilaterally on SLNs and after two weeks recovery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…For example, Marx et al found that bisphosphonate drugs (BPs) can cause drug-induced necrosis of the jaw [31]. Another drug named calcitonin offers anti-osteoporosis effects by inhibiting the functions of osteoclasts [32], but some research also found that calcitonin inhibits the functions of both osteoblasts and osteoclasts and may decrease the body's bone formation capabilities [33]. Another treatment for osteoporosis is estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Marx et al found that bisphosphonate drugs (BPs) can cause drug-induced necrosis of the jaw [31]. Another drug named calcitonin offers anti-osteoporosis effects by inhibiting the functions of osteoclasts [32], but some research also found that calcitonin inhibits the functions of both osteoblasts and osteoclasts and may decrease the body's bone formation capabilities [33]. Another treatment for osteoporosis is estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have experimentally confirmed that electrical stimulation with direct currents has a therapeutic effect on osteoporosis. In a study by Iimura et al, the researchers demonstrated that electrical stimulation of the superior laryngeal nerve fibers in rats resulted in calcitonin secretion [ 76 ]. Iimura et al also found a statistically significant increase in BMD in the tibial and femoral metaphysis in rats under chronic electrical stimulation versus the control group [ 76 ].…”
Section: Therapeuticsmentioning
confidence: 99%
“…In a study by Iimura et al, the researchers demonstrated that electrical stimulation of the superior laryngeal nerve fibers in rats resulted in calcitonin secretion [ 76 ]. Iimura et al also found a statistically significant increase in BMD in the tibial and femoral metaphysis in rats under chronic electrical stimulation versus the control group [ 76 ]. In another study conducted by Yuen-Chi Lau et al, the researchers applied electrical stimulation to the dorsal root ganglion in rats.…”
Section: Therapeuticsmentioning
confidence: 99%
“…At present, many animal experiments have confirmed that DC has a therapeutic effect on osteoporosis ( Table 4 ). Kaori Iimura et al discovered that chronic stimulation of the superior roaring nerve in rats with implanted electrodes stimulated the thyroid to release calcitonin and partially ameliorated bone loss in OVX (ovariectomy) rats [ 69 ]. Roy Yuen-Chi Lau et al illustrated that electrical stimulation of the dorsal root ganglion of rats using an implantable micro-electrical stimulation system can stimulate the secretion of calcitonin gene-related peptides and inhibit osteoporosis as well [ 70 ].…”
Section: DC For Osteoporosismentioning
confidence: 99%